PERILAKU KUAT TEKAN BETON DENGAN ABU CANGKANG SAWIT SEBAGAI PENGGANTI SEBAGIAN SEMEN - Martin Lerry; Elhusna Elhusna; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2019)
The aim of this research was to know if palm oil (Elaeis Guineensis) fly ash could replace some cement. Palm oil fly ash which used was taken from palm oil factory PT.Sandabi Indah Lestari at North Bengkulu. The research was directed according to SK SNI-T-15-1990-03, used cylinder specimens, water cement ratio 0.5, and slump value 30-60 mm. The research was substituted partly cement with palm oil fly ash as 0%, 5%, 10%, 15%, and 20% of cement weight. There were two types of sand used in the research namely oceanic sand and mountain sand. All the samples had the same caring until 28 days when the compression test carried out. Concrete compression strength showed decreasing trend. The strength decreased as theincreasing of percent of palm oil fly ash used. The maximum decreases compared to the strength of concrete without the ash were 40% when the concrete used mountain sand and 45,19% when it used oceanic sand.